B23 Immune dysfunction in HD human myeloid cells is caused by NFκB pathway dysregulation and is reversed by lowering HTT levels. (29th August 2012) - Träger, U; André, R; Lahiri, N; Magnusson, A; Pfister, E; Weiss, A; Grüninger, S; Antoniou, M; Bates, G; Muchowski, P; Björkqvist, M; Ostroff, G; et al.
Abstract : Background: Altered innate immune responses are observed in HD, with hyper-reactive central and peripheral immune cells producing increased levels of pro-inflammatory cytokine in HD patients. Bone marrow transplantation studies and KMO inhibitor administration have both shown that the immune system is a modifier of HD progression. However, a mechanistic understanding of how this relates to mHTT expression has been lacking. Aim: Characterise the abnormal function of peripheral myeloid cells and examine alterations in signalling pathways responsible for those changes. Results: The production of pro-inflammatory cytokines in response to LPS was elevated in both monocytes and macrophages from HD patients. Induction of mHTT exon 1 expression in a myeloid cell line showed that the hyper-reactive cytokine production is caused by a cell intrinsic effect of exon 1 mHTT expression. Significant changes in the expression levels of several key molecules in the NFκB pathway, such as IRAK1 and AKT1, were identified using PCR signalling arrays. IκB, the endogenous inhibitor of NFκB activity, was more rapidly degraded following LPS stimulation in HD patients compared to controls, potentially leading to increased NFκB activity and altered gene expression. A direct interaction between HTT and IKKγ was demonstrated by co-immunoprecipitation, suggesting the possibility of a scaffolding function of HTT in the NFκB pathway that may be altered by an expanded polyQ-repeat. Knocking-down total HTT protein levels using GeRP-delivered siRNA in human HD macrophages led to a reduction of cytokine production by LPS-stimulated HD cells. Conclusions: Taken together, these data suggests that the dysfunction of primary myeloid cells from HD patients is directly caused by the expression of mHTT and its effects on the NFκB pathway. Lowering HTT levels in human macrophages can at least partially restore normal cell function, underlining the importance of HTT-lowering as a therapeutic approach.